LUNASKA neutrino search with the Parkes and ATCA telescopes - Bray, J.; Ekers, Ronald; Protheroe, R.; James, C.; Phillips, C.; Roberts, P.; Brown, A.; Reynolds, J.; McFadden, R.; Aartsen, M. (2013)
The Moon is used as a target volume for ultra-high energy neutrino searches with terrestrial radio telescopes. The LUNASKA project has conducted observations with the Parkes and ATCA telescopes; and, most recently, with both of them in combination. We present an analysis of the data obtained from these searches, including validation and calibration results for the Parkes-ATCA experiment, as well as a summary of prospects for future observations. © 2013 AIP Publishing LLC.